MODEL ANTRIAN PENGURUSAN SURAT KETERANGAN JASMANI, ROHANI, DAN NAPZA DI RSUD dr. ABDOER RAHEM SITUBONDO MENGGUNAKAN PETRI NET DAN ALJABAR MAX-PLUS - Indriyani, Desi; Santoso, Santoso; Sari, Lisma Dian Kartika; Wahyuni, Fatmawati Sri (CERMIN: Jurnal Penelitian, 2025)
Healthcare service queues are one of the most common discrete event problems encountered in hospitals, including the service for obtaining the Physical, Mental, and Drug-Free Health Certificate at RSUD dr. Abdoer Rahem Situbondo. This study aims to model the queuing system for that service using the Petri Net and Max-Plus Algebra approaches in order to estimate optimal service time. The secondary data used in this research is the service process flow of Session 1 at 08:00 AM, obtained from the official website of RSUD dr. Abdoer Rahem Situbondo. The methods employed include literature review, Petri Net modeling, Max-Plus Algebra formulation, and simulation using PIPE 4.3.0 software. The results show that the Petri Net model successfully represents the service sequence systematically, and the Max-Plus Algebra model can estimate the service time accurately. If a patient arrives at 08:00 AM, the estimated total time required to complete the entire process is 195 minutes or 3 hours and 15 minutes, indicating that the patient will complete the process at 11:15 AM. The findings of this research can serve as a reference for improving administrative service efficiency in hospitals, particularly in processing the Physical, Mental, and Drug-Free Health Certificate at RSUD dr. Abdoer Rahem Situbondo.